Peran Produk Financial Technology dalam Kinerja Keuangan Perusahaan - Lena Sepriani; Candy Candy; Alice Alice; Hendru Hendru (Jurnal Inovasi Bisnis dan Kewirausahaan, 2022)
Fintech innovation is one of the corporate strategies to increase profitability and firm performance. This study examines the firm's performance before and after the company launches fintech products. The sample of this study is the companies running fintech innovations for two years and previously also operated without them, which consisted of 19 companies from 51 licensed e-money providers in Indonesia. This limitation occurs because there are still many companies that have not published their financial statements. The event study method and paired sample t-test were used to test the research hypothesis. The results indicate a significant change in return on assets (ROA) but no significant change in return on equity (ROE). This study can contribute to the fintech industry regarding the profitability impact on companies before and after launching fintech products in Indonesia